From the Amelioration of a NADP+‐dependent Formate Dehydrogenase to the Discovery of a New Enzyme: Round Trip from Theory to Practice. Issue 9 (19th March 2020) - Robescu, Marina Simona; Rubini, Rudy; Beneventi, Elisa; Tavanti, Michele; Lonigro, Chiara; Zito, Francesca; Filippini, Francesco; Cendron, Laura; Bergantino, Elisabetta
Abstract: NADP + ‐dependent formate dehydrogenases (FDHs) are biotechnologically relevant enzymes for cofactors regeneration in industrial processes employing redox biocatalysts. Their effective applicability is however hampered by the low cofactor and substrate affinities of the few enzymes described so far. After different efforts to ameliorate the previously studied Gra FDH from the acidobacterium Granulicella mallensis MP5ACTX8, an enzyme having double (NAD + and NADP + ) cofactor specificity, we started over our search with the advantage of hindsight. We identified and characterized Gra FDH2, a novel highly active FDH, which proved to be a good NAD + ‐dependent catalyst. A rational engineering approach permitted to switch its cofactor specificity, producing an enzyme variant that displays a 10‐fold activity improvement over the wild‐type enzyme with NADP + . Such variant resulted to be one of the best performing enzyme among the NADP + ‐dependent FDHs reported so far in terms of catalytic performance. Abstract : The race towards NADP + ‐specificity : a new FDH was identified and successfully engineered in order to switch its cofactor specificity.